(untitled) (Dhaka University Journal of Biological Sciences, 2021)
Effects of organic manures on growth and yield of lettuce (Lactuca sativa L.) and nutrient accumulation in its leaves was examined. The experiment was conducted in a completely randomized design (CRD) replicated thrice with ten treatments involving nine organic manures and a control treatment. Growth parameters viz. plant height, leaf number, leaf length, leaf area, leaf area index and fresh and dry weight of leaf, stem and root were assessed. The highest height (23.69 cm), longest leaf (32.18cm), leaf area (5883.43cm2), leaf area index (6.434), fresh weight (85.41 g) and dry weight (42.73 g) were found in Payel organic manure. The maximum leaf number (27) was recorded in Approshika organic manure. The maximum content of nitrogen (6.12%), phosphorus (1.83%), potassium (4.11%) and Sulphur (1.69%) were observed in Payel organic manure. The best growth performance and nutrient accumulation was observed in Payel organic manure. Dhaka Univ. J. Biol. Sci. 30(2): 159-168, 2021 (July)